Different Proportion of Mocaf (Modified Cassava Flour) and Soy Flour (Glycine Max L.) towards Chemical and Organoleptic Quality of Cookies - Wono, Cynthia Febrina; Djauhari, Arlin Besari; Hariyani, Nunuk (Food Science and Technology Journal (Foodscitech), 2019)
Cookies are snacks made by the basic ingredients of Mocaf and soy flour. The usage of both expects higher content of protein and fibre, compared to the general cookie. This research aims to understand the influence of both flour's proportion towards cookies' chemical quality and organoleptic. This research utilises Factorial Randomised Design using two factors such as proportions of Mocaf and soy flour. Every treatment is conducted three times. The determination of the best treatment off all parameters are performed through effectivity test. Factors aforementioned are each divided by three levels, which are Mocaf flour proportions as many as 55%, 50%, and 45% and soy flour proportions as many as 10%, 15%, and 20%. Every treatment is conducted three times. The treatment of the combination of 55% Mocaf flour and 20% soy flour (M3K3) is the best treatment, according to the effectivity test of Result Value (RV) which is 0.57. It is also supported by the testing of parametric criteria such as protein content (3.74%), fibre content (1.91%), water content (2.27%), ash content (1.92%), flavour (5.4, somewhat like), aroma (5, somewhat like), colour (5.3, somewhat like), and crunchiness (5.5, like).